Anatomic variations of the celiac trunk and hepatic arterial system with digital subtraction angiography - Zagyapan, Ragıba; Kürkçüoğlu, Ayla; Bayraktar, Ahmet; Pelin, Can; Aytekin, Cüneyt (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Anatomical variation of the abdominal arteries is important. Historic and modern anatomists, radiologists, as well as surgeons have reported and accumulated anatomical variations with a morphological and clinical interest. During graft procurement and reconstruction, accidental injury of the hepatic artery is more likely in the presence of hepatic arterial variation, which can be a common clinical entity. During cadaveric dissection and diagnostic radiological imaging, various types of vascular anomalies are frequently found in human abdominal viscera, especially the celiac trunk. The aim of the present study is to determine anatomical variations in the celiac trunk and hepatic arterial system. Materials and Methods: Digital subtraction angiography data were collected from 152 consecutive donor patients (103 males and 49 females, aged between 6 and 77 years) who underwent orthotopic liver transplantation. Results: We examined the anatomy of the celiac trunk in a total of 152 consecutive patients. In total, 62.5% (95/152) of patients showed the classical trifurcation of the celiac trunk. Variant right hepatic arteries arising from the superior mesenteric artery were observed in 17.8% (27/152), the hepatic arteries arising from the left gastric artery were found in 13.1% (20/152), and common hepatic arteries arising from the superior mesenteric artery were observed in 6.6% (10/152) of patients. Conclusion: These data are useful for planning and performing surgical and radiological procedures of the upper abdomen.